Luther and the War against the Turks - Forell, George Wolfgang (Church history, 1945)
Modern psychoanalysis tells us that disease is the touchstone of the healthy mind. What is true in the realm of psychology is not less true in the realm of ethics. The most terrible disease in the realm of human relations is war and so we can say that war is the touchstone of a healthy ethical system. In its attitude toward war the weakness of an ethical system is revealed. In the war situation an ethical system is revealed as basically unrealistic if it proves unwilling to face the actual situation and therefore uses the escape of absolute pacifism. It is revealed as basically immoral if it condones any war to such an extent that it loses sight of sin and injustice and makes of that war a holy war or a crusade.